MODEL PENGEMBANGAN BAHAN AJAR BAHASA INGGRIS BERBASIS PENDEKATAN MULTISENSORI PADA SISWA SEKOLAH DASAR - Mujiono Mujiono (Jurnal Bahasa Lingua Scientia, 2012)
This research is intended to develop a model of multi sensory-based English teaching resource for the students of elementary school, and to measure the effectiveness of that resource for the fifth graders at SDN Sukun III Kota Malang. There are six steps to develop that teaching resources: (a) identifying the teaching objectives, (b) analyzing the teaching objectives, (c) identifying students’ behaviors and characteristics, (d) formulating the specific teaching objectives, (e) formulating the test items, and (f) developing the learning strategy. The statistical analysis of the hypothesis testing results in p = 0.000 < 0.05. It means that the use of this sort of English teaching resources to the fifth graders of SDN Sukun III is more effective than the use of the commonly-used English teaching resources.